2022
DOI: 10.1111/ijfs.15960
|View full text |Cite
|
Sign up to set email alerts
|

Powder structure and gelation behaviour of debranched cassava starches prepared with and without incubation

Abstract: The effect of incubation after debranching on the powder structure and gelation behaviour of debranched cassava starch (DBCS) was investigated. The DBCS samples were prepared by debranching 10% (w/v) cassava starch with pullulanase at 55 °C for 24 h, then incubated at 4 °C for 0, 1, 4, 24 and 72 h and recovered by precipitation with ethanol. The unincubated DBCS appeared as small, sponge-like aggregates with a rough surface, while the incubated DBCS powders were considerably larger, looked denser and had a smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The obtained DBCS exhibited a degree of hydrolysis of 4.35%, comprising 65.9% A chains, 22.1% B1 chains and 9.5% B2 + B3 chains from amylopectin, along with 2.5% longer chains from amylose with an average chain length of 23.5. The powders demonstrated a B-type crystal structure with 23% crystallinity and contained 31.2% resistant starch (RS) and 7.2% slowly digestible starch, as reported by Sari et al (2022). Sucrose was purchased from Ajax Finechem (NSW, Australia), and salt (sodium chloride) was purchased from QRec (New Zealand).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The obtained DBCS exhibited a degree of hydrolysis of 4.35%, comprising 65.9% A chains, 22.1% B1 chains and 9.5% B2 + B3 chains from amylopectin, along with 2.5% longer chains from amylose with an average chain length of 23.5. The powders demonstrated a B-type crystal structure with 23% crystallinity and contained 31.2% resistant starch (RS) and 7.2% slowly digestible starch, as reported by Sari et al (2022). Sucrose was purchased from Ajax Finechem (NSW, Australia), and salt (sodium chloride) was purchased from QRec (New Zealand).…”
Section: Methodsmentioning
confidence: 99%
“…International Co., Ltd, Bangkok, Thailand) was purchased at a local market in Bangkok, Thailand. The DBCS utilised in this study was sourced from the same batch as reported by Sari et al (2022). Following the debranching of cassava starch using pullulanase, the resulting debranched product underwent a 24-h incubation at 4 °C before precipitation with ethanol and subsequent drying.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations